Eldercare in the Singapore Real Estate Market #x2013; An Emerging Perspective (Global Journal of Management and Business Research, 2021)
Aging has become one of the primary concerns of the world in the present time. The proportion of people in society at extreme old age is higher compared to the last decades (World Health Organization, 2011, p. 1). According to the United Nations, by 2050, the number of people above 60 will double, and there is a high chance that it will increase three times by 2100 (United Nations, 2015, p. 1). Hence, with the increasing number of older adults, the demands to address their needs in healthcare and real estate will increase as well #x2013; both quantitatively and qualitatively. This situation prompted the author to ask the following questions: What are the characteristics of real estate that address the needs of the aging society? Which Singaporean mechanisms can amalgamate the healthcare domain requirements and create a market and robust solutions for eldercare in real estate? In this paper, the author analyses various research overviews and case studies from past decades which discussed older people#x2019;s environment and policies designed by public authorities. In addition, the author used the United Nations Economic Commission for Europe variables to project the real estate market prospective for senior people in Singapore.
Keywords: aging; healthcare and real estate needs; real estate market; adaptation